Health effects and occurrence of dietary polyamines: a review for the period 2005-mid 2013 - Kalač, Pavel (Food chemistry, 2014)
This review continues a previous one (Kalač & Krausová, 2005). Dietary polyamines spermidine and spermine participate in an array of physiological roles with both favourable and injurious effects on human health. Dieticians thus need plausible information on their content in various foods. The data on the polyamine contents in raw food materials increased considerably during the reviewed period, while information on their changes during processing and storage have yet been fragmentary and inconsistent. Spermidine and spermine originate mainly from raw materials. Their high contents are typical particularly for inner organs and meat of warm-blooded animals, soybean and fermented soybean products and some mushroom species. Generally, polyamine contents range widely within the individual food items.
Keywords: Spermine; polyaminy; spermin; Biogenic Amines; Humans; Food; Health effects; biogenní aminy; Spermidine; dějiny 21. století; lidé; Biogenic amines; Diet; dieta; History, 21st Century; Polyamines